Transition in Older Parent–Adult Child Relations in U.S. Chinese Immigrant Families. (5th November 2019) - Guo, Man; Stensland, Meredith; Li, Mengting; Beck, Todd; Dong, Xinqi
Abstract: Background and Objectives: The family fundamentally underpins the immigration and acculturation processes. But most existing research on acculturation focuses on individual instead of family experience. Guided by Berry's acculturation theory and Intergenerational Solidarity Theory, this study examined continuity and changes in parent–adult child relations of older Chinese immigrants over a 2-year period, and their implications for older adults' depression and quality of life (QoL). Research Design and Methods: Participants included 2, 605 older Chinese immigrants from the Population Study of Chinese Elderly in Chicago (PINE). Latent Transition Analysis (LTA) was used to identify transitions in multidimensional parent–child relations over time. Negative binomial and logistic regressions were used to examine the influence of family transitions on depression and QoL, respectively. Results: LTA revealed five types of family relations: traditional, modified traditional, coresiding-unobligated, independent, and detached . Over 40% of the respondents shifted to a different relation type, with more families classified as modified traditional or independent over time. Transitioning into modified traditional relations or out of detached relations was associated with fewer depressive symptoms and better QoL at the follow-up. Transitioning into independent relation was associated with more depressive symptoms over time. Discussion and Implications: Parent–child relations among Chinese older immigrants demonstrate significant complexity, including both heterogeneity and fluidity. Better well-being of these older adults seems to stem from the optimal combination of retaining the supportive heritage culture and embracing the host society's instrumental cultural elements. Services to this population need to include the family context in assessment and interventions.